Pentose phosphate pathway in health and disease: from metabolic dysfunction to biomarkers - Ramos, Rúben José Jesus Faustino (2014)
Tese de mestrado, Análises Clínicas, Universidade de Lisboa, Faculdade de Farmácia, 2013